ADAPTATION STRATEGIES OF IRRIGATED AND RAINFED RICE FARMERS IN FACING CLIMATE CHANGE IN SOUTH LAMPUNG DISTRICT - Ibrohim Saputra; Fembriarti Erry Prasmatiwi; Zainal Abidin; Agus Setiawan (Jurnal Ilmiah Mahasiswa Agroinfo Galuh, 2022)
Rice is is one of the food crops sub-sector commodities that are most affected by climate change. The negative impact of climate change on lowland rice is the decline in production and productivity due to changes in planted area and harvested area. The purposes of this study is to analyze the adaptation strategies of irrigated and rainfed farmers in facing climate change. The study was conducted in Palas District, Candipuro District, and Sidomulyo District, South Lampung Regency from June to September 2020. The sample in this study consisted of 100 farmers with details of 50 irrigated rice farmers and 50 rainfed rice farmers. Data were analyzed descriptively, presented in percentage form and then narrated. The results showed that the adaptation strategies adopted by irrigated and rainfed rice farmers in the face of climate change include adapting the use of rice varieties, adjusting planting time, using boreholes, diversifying income outside the agricultural sector, and participating in agricultural insurance programs. The majority of irrigated and rainfed rice farmers have the same pattern in implementing adaptation to climate change, but irrigated rice farmers apply more adaptation strategies in the form of adapting the use of rice varieties, using boreholes, diversifying income outside the agricultural sector, and participating in agriculture insurance program.